Septic pericardial disease and mediastinal abscessation in a cat with an intrathoracic needle foreign body. Issue 5 (20th April 2022) - Bahlmann, Kaitlin N.; Kennedy, Christopher R.; Bandt, Carsten
Abstract: Objective: To describe the successful management of a cat with an intrathoracic sewing needle foreign body and septic pericardial effusion. Case Summary: A 10‐year‐old neutered female domestic longhair cat was referred for an intrathoracic metallic foreign body identified via thoracic radiography. Two weeks prior, the cat may have ingested a sewing needle. She was presented hemodynamically unstable; point‐of‐care thoracic ultrasound identified pericardial effusion with right atrial tamponade. Pericardiocentesis stabilized hemodynamic parameters. The effusion was grossly purulent, and bacterial culture grew an Actinomyces sp. The cat underwent a median sternotomy to remove the foreign body, debride associated mediastinal abscesses, and perform a partial pericardiectomy. Over the next 10 days, the cat was managed in hospital with a left unilateral thoracostomy tube and intermittent lavage of the pleural cavity. The cat was discharged, and follow‐up at 7 days showed no evidence of pericardial or pleural effusion. New or Unique Information Provided: Contrary to previous reports, this case shows that extra‐gastrointestinal, specifically intrathoracic, sewing needle foreign bodies can cause significant morbidity in cats. To the authors' knowledge, this report is the first to describe septic pericardial disease resulting from documented foreign body ingestion in the cat. It is also the first case report of successful surgical management of mediastinal abscessation in the cat.